Diseño de una planta de poscosecha de frutas y hortalizas en la parroquia Chuquiribamba del Cantón y Provincia de Loja - González González, Jackeline Fernanda (2021)
Postharvest is a process of great importance to reduce the losses of agricultural products and obtain quality and safe food from harvest to consumption as a result. In Ecuador, 40% of production is lost due to the lack of good technical management, lack of infrastructure and equipment, in view of this, it was proposed to design a post-harvest plant for fruits and vegetables in the Chuquiribamba parish to be able to offer to markets fixed products in quantity and quality at higher prices; To achieve this, it began with a market study in a population of 104 families to determine the unsatisfied demand, price and marketing system, then a technical study was carried out to determine the size, location and engineering of the postharvest plant complying with the Good Manufacturing Practices (BPM), and finally, the investment costs for the acquisition of machinery and equipment were determined. From the results it is obtained that the offer is made up of 20 products including fruits and vegetables that are produced in greater quantity in the parish, which are sold in markets and free fairs under unfavorable conditions, with variations in prices. The demand corresponds to the supermarkets and micro-markets of the city of Loja, which currently purchase agricultural products within the city without guarantee of quality; Due to this, these establishments agree to buy products with postharvest handling from Chuquiribamba. With the implementation of the post-harvest plant, it is projected to cover between 40 and 90% of the market demand under study for the fifth year and a direct marketing system at stable prices, with a capacity of 200 kg / hour, which will be located in the San Vicente Ferrer neighborhood and designed based on the size of the equipment, a production process adapted to each product and the needs of the operators taking into account the GMP; for which an investment of US $ 83,176.86 is needed for the acquisition of machinery and equipment. This proposal will allow to have a new alternative to improve the post-harvest and commercialization processes that will benefit the economy of the farmers of the parish and their families. Keywords: equipment, Good Manufacturing Practices (GMP), supply, demand, quality and safety